Comparing the Impact of Credit Constraints on the Growth of SMEs in a Transition Country with an Established Market Economy - John Hutchinson; Ana Xavier (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2004)
In this paper we compare the role of internal finance on the growth of firms between a leading transition country, Slovenia and an established market economy, Belgium. We find that firms in Slovenia are more sensitive to internal financing constraints than their Belgian counterparts. This would suggest that although Slovenian firms are no longer recipients of soft budget constraints, capital markets are not yet functioning properly.
Keywords: G32; P2; L6; 330; financial constraints; transition economics; manufacturing; Verschuldungsrestriktion; Eigenkapital; Verarbeitendes Gewerbe; Vergleich; Slowenien; Belgien